A new approach of crossdocking in supply chain of bangladesh (International Journal of Scientific Research and Management (IJSRM), 2013)
This study focuses on the process of selecting a cross-docking environment to determine cross-docking locations of incoming unit loads. It helps to minimise supply chain cost and lead time with best efficiency and effectiveness. This model is applicable for various types of goods. This model gives better solution for determining supply chain network design. An algorithm has been developed with considering some variables related to cross-docking operation. Two case studies have been analysed in two different company’s supply chain system and make recommendations for reducing supply chain network cost. Furthermore, the paper shows that the approach is superior to a commonly used heuristic method also the benefit using crossdocking over distribution centre and how to select cross-docking environment or distribution centre.